Evaluating learning strategies in high school students - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Petcu, Maria (Technium Social Sciences Journal, 2022)
This study aims to address the assessment of learning strategies, as they are considered to be particularly important in the educational process. The principle of the theory that supports the substance of our work is that the educator and the educated are agents who become effective only in conditions of individual and bilateral co-balancing, in a common pedagogical field, determined by a number of variables specific to school space and time. The quality of the didactic act is measured by the efficiency of the training of students’ personality competencies, context in which the combination of classical, traditional and modern strategies, according to the principle of complementarity, is a requirement and at the same time an essential condition of teaching and learning. Educational disciplines acquire educational strength through the action of teachers who use methodological and psychopedagogical knowledge operationalized in specific ways and techniques of action as a defining element of professional competence, methodical training makes it possible to transform general principles into teaching strategies, design realization and evaluation techniques.